A PERSON-FOCUSED HEALTH PROMOTION AND WELLNESS APPROACH TO EXTEND HEALTHSPAN IN ADULTS WITH DISABILITIES: THE CHAMP - D. (11th November 2018) - Heyn, P C; Tagawa, A; Pan, Z; Carollo, J
Abstract: This presentation will discuss the findings from a person-focused health and wellness approach to healthspan called Comprehensive Health Assessment and Motivation Program for Individuals with Disabilities (CHAMP-D). The CHAMP-D is a health passport platform tool designed to screen early chronic disease development associated to accelerated aging (i.e. metabolic syndrome, sedentary behavior, obesity and memory impairment) with the goal to empower self-health control and management in adults with cerebral palsy from the Cerebral Palsy Adult Transition and Longitudinal Study (CPAT). Data from 72 participants and CHAMP-D follow up data will be presented. Since participating in the CHAMP-D, 57.9% of the participants reported increased physical activity levels, 57% made healthy changes to their diet, and 55% showed the health recommendations to a health professional. CHAMP-D health passport seems to have great potential to intervene in the process of early disease development in individuals with disabilities and to decelerate their early aging process.